The influence of life skills education through UMKM crafts making beautiful Besek on increasing work motivation and fulfilling family needs in Pucanganak village, Tugu district, Trenggalek regency - Haryati, Sri; Riyanto, Yatim; Lestari, Gunarti Dwi (Universitas Malikussaleh, 2023)
The purposes of this research are (1) to find out the effect of life skill education through SMEs in the craft of making beautiful besek on work motivation. (2) Knowing the effect of life skills education through MSME crafts making beautiful besek on meeting family needs. This research uses a type of quantitative research with correlational methods. The number of research samples is 123 students. There are two variables in this study, namely the independent variable and the dependent variable. The independent variable is the treatment of this study, namely Life Skills Education (life skills). The dependent variable is work motivation and meeting family needs. The data collection technique used is a questionnaire. Questionnaires are used to find out the results of life skills education, work motivation and meeting family needs. The hypothesis testing data analysis technique is simple linear regression analysis. The results and analysis of research data were obtained as follows: (1) The results of the linear regression analyze test showed a significance value of 0.000 or Î± <0.05 (0.000 < 0.05), so it could be concluded that there was an effect of Life Skills Education on work motivation in the village of Pucanganak, Tugu sub-district, Trenggalek Regency. (2) The results of the linear regression analyze test have a significance value of 0.000 or Î± < 0.05 (0.000 <0.05), so it can be concluded that there is an influence of Life Skills Education on fulfilling family needs in Pucanganak Village, Tugu District, Trenggalek Regency.